2007
DOI: 10.1063/1.2715042
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous charge transfer at organic-organic homointerfaces to establish thermodynamic equilibrium

Abstract: The energy level alignment of ␣ , -dihexylsexithienyl ͑DH6T͒ mono-and multilayers on tetrafluorotetracyanoquinodimethane ͑F4-TCNQ͒ precovered Ag͑111͒ and polycrystalline Au substrates was investigated with ultraviolet photoelectron spectroscopy. For certain F4-TCNQ precoverages molecular level pinning at DH6T monolayer-multilayer homointerfaces was observed. The pinning behavior shows that thermodynamic equilibrium can be established across hexyl chains via charge transfer, indicating the limited use of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 16 publications
1
23
1
Order By: Relevance
“…A similar spontaneous charge transfer at an organic/ organic homointerface due to an orientational transition has been observed before, 44 however with opposite direction. For PFP in the herringbone arrangement the small transport gap ͑estimated to be ϳ2.10 eV͒ ͑Ref.…”
Section: Discussionsupporting
confidence: 79%
“…A similar spontaneous charge transfer at an organic/ organic homointerface due to an orientational transition has been observed before, 44 however with opposite direction. For PFP in the herringbone arrangement the small transport gap ͑estimated to be ϳ2.10 eV͒ ͑Ref.…”
Section: Discussionsupporting
confidence: 79%
“…1,2 Intensive research efforts are being carried out to understand the energy level alignment in organic heterostructures with the aim of achieving full control over interface energetics. [3][4][5][6] Recently, the importance of intramolecular polar bonds ͑IPBs͒ on the electronic structure in organic/organic heterostructures was realized and it was demonstrated that IPBs can significantly impact the ionization energy ͑IE͒ of ordered molecular assemblies. 7,8 The IE is commonly believed to be a key parameter for energy level alignment.…”
mentioning
confidence: 99%
“…[1][2][3][4] They yield improved device performance due to organic/organic ͑O/O͒ charge transfer complex ͑CTC͒ formation in the codeposited thin films, which increases the layer conductivity and lowers the hole injection barrier ͑HIB; defined as energy difference between E F and the highest occupied molecular orbital onset͒ at the anode ͑p-type doping͒. Strong electron acceptors can also be used to precisely adjust the energy levels at organic/metal ͑O/M͒ interfaces, 5,6 even in the absence of doping. In this case, an O/M CTC ͑Ref.…”
mentioning
confidence: 99%
“…7͒ is formed, which increases the effective substrate surface potential and thus reduces the HIB for any subsequently deposited organic material. 5,6 Note that HIB lowering due to O/M CTC formation may be misinterpreted as p-type doping of the organic layer ͑O/O CTC͒ because a shift of the donor energy levels toward the substrate Fermi level ͑E F ͒ occurs in both cases. Acceptors are often small molecules like tetrafluoro-tetracyanoquinodimethane ͑F4-TCNQ͒ ͓chemical structure shown in Fig.…”
mentioning
confidence: 99%